(untitled) (Global Journal of Management and Business Research, 2023)
This article examines the workplace experiences of young professionals as they integrate into management roles and the potential impact these have on developing their careers The methodology is based on a qualitative research study using one-on-one interviews with 61 participants The findings illuminate a wide range of workplace experiences that can either facilitate or complicate their integration This study contributes to documenting the workplace experiences of young managers early in their careers as well as the persistence of certain gender issues